Implementasi Pendekatan Represif dalam Menumbuhkan Karakter Disiplin Santri Putri Berdasarkan Perspektif Teori Behavioristik di Madrasah Diniyah Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan - Eka Fitriani; Rina Setyaningsih; Nur Widiastuti (Departement of Mathematics Education, 2024)
The point of this examination is to break down the execution of the harsh methodology in developing the disciplinary person of female santri in view of the point of view of behavioristic hypothesis at Madrasah Diniyah Hidayatul Mubtadiin Islamic Life experience School Jati Agung South Lampung in 2023/2024, to dissect the supporting and hindering elements for the execution of the abusive methodology in developing the disciplinary person of female santri in light of the viewpoint of behavioristic hypothesis at Madrasah Diniyah Hidayatul Mubtadiin Islamic Live-in School, Jati Agung, South Lampung in 2023/2024. This kind of exploration is subjective. The technique utilized is graphic examination. Trademark (Field Exploration). Information assortment procedures use perception, meetings and documentation. Information examination incorporates information decrease, information show and information legitimacy. inspectors use information believability tests or information legitimacy utilizing observational steadiness procedures and triangulation. The aftereffects of the examination show that the Abusive Methodology applied at the Hidayatul Mubtadiin Islamic Life experience School depends on the standards of behavioristic hypothesis as observes: Orderly, arranged and coordinated exercises, making rules, severe oversight and giving authorizations, joined with participatory and persuasive methodologies, assessment and criticism return. In view of exploration discoveries, the supporting variables are dynamic cooperation and great positive mindfulness of understudies, the job of parental figures, managers and educators, clear and steady standards and guidelines. while the repressing elements are: understudies who need discipline, varieties behind the scenes of understudies, absence of comprehension of the worth of discipline. The consequences of involving the execution of a harsh methodology in developing the trained person of female understudies show that this strategy is powerful as far as expanding understudy discipline, yet it should be done cautiously to keep away from pessimistic effects.